2016
DOI: 10.1016/s0140-6736(15)00516-4
|View full text |Cite
|
Sign up to set email alerts
|

The World report on ageing and health: a policy framework for healthy ageing

Abstract: Although populations around the world are rapidly ageing, evidence that increasing longevity is being accompanied by an extended period of good health is scarce. A coherent and focused public health response that spans multiple sectors and stakeholders is urgently needed. To guide this global response, WHO has released the first World report on ageing and health, reviewing current knowledge and gaps and providing a public health framework for action. The report is built around a redefinition of healthy ageing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
1,283
0
66

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,931 publications
(1,475 citation statements)
references
References 40 publications
18
1,283
0
66
Order By: Relevance
“…For example, a study showed that aging is related to a high burden from cardiovascular diseases and is thus a major global concern 4. In addition, length of hospital stay (LOHS) has implications given that it varies by region and medical system 5, 6, 7.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study showed that aging is related to a high burden from cardiovascular diseases and is thus a major global concern 4. In addition, length of hospital stay (LOHS) has implications given that it varies by region and medical system 5, 6, 7.…”
Section: Introductionmentioning
confidence: 99%
“…Greater longevity can be considered a success story for mankind 3 , and these extra years of life allow people to plan their future in a different manner to previous generations, depending on one central element: health 4 .…”
Section: Introductionmentioning
confidence: 99%
“…A World Health Organization (WHO) report on ageing and health, published in 2015 (WHO 1 ), suggests there should be a shift in focus from diseases and morbidity to functional ability (1), and therefore future studies of ageing should be more specific when defining healthy ageing and, in addition to describing patterns of morbidity and mortality, it is advisable to look at physical and cognitive function (1,2). Functional ability is the key for living good independent lives throughout their life course and obtaining a high quality of life (QoL) (1).…”
Section: Introductionmentioning
confidence: 99%